Latin Monetary Union and Balkan Monetary Systems, 1865-1912/1914 - Nenovsky, Nikolay; Ndao, Souleymane; Vaslin, Jacques Marie (Research Papers, 2017)
The study presents the Latin Monetary Union (1865-1927) and its influence on Balkan monetary systems. The reason for writing the study is the publication of the book of the French economist Lucien Gillard “L’Union Latine, une experience de souverainetes monetaires partagees (1865-1927)”, Classiques Garnier, Paris, 2017. The article puts forward the hypothesis of the contradiction of the economic structure of the periphery with the monetary regime of the European core. The role of the agio, its relation to public finances, interest rates, as well as the putting into circulation of gold backed banknotes are discussed.